Agronomic performance, biomass production, and nutrient value of three napier grass cultivars (Pennisetum purpureum) in highland area - Sidik Prasojo Yogi; Pastawan Viagian; Prasetyo Bayu; Kamal Mustafa; Khoirul Anwar Muhammad; Adi Prastyo Riski; Iqbal Faruqi Muhammad; Ishigaki Genki (BIO Web of Conferences)
The study aims to determine the agronomic performance, biomass production, and nutrient value of three Pennisetum purpureum cultivar (Biovitas, Pakchong, and Mott) in 1000 meters above sea level (asl) highland area of Petungkriyono, Pekalongan, Central Java, Indonesia. The grasses were planted using vegetative stems and maintained for four months, following completely randomized design (CRD) with four replications for each cultivar. Agronomic performance was assessed before harvested. Napier grass was harvested to investigate the biomass production and nutrient values, including organic matter, crude protein, crude protein yield, crude fibre, and crude fat. Pakchong had the highest biomass and crude fiber content. Biovitas exhibited the highest agronomic performance, with superior plant height, leaf length, leaf width, and stem diameter, as well as the highest nutrient values in term of organic metters. Mott showed the highest tiller number and crude protein content among the cultivars. The distinct strength of each cultivar indicates their potential suitability for various agricultural applications in highland regions.